Strength of materials: for engineering degree, diploma and A.M.I.E. students - Ramamrutham, S; Narayanan, R (New Delhi: Dhanpat Rai Publications, 2020)
About the book: This edition incorporating additional theory with many solved problems. Chapters on simple stresses and strains, deflection of beams, torsion of shafts and columns and struts have been enlarged with additional solved problems. The present edition contains over 1600 fully solved problems besides a large number of problems set for exercise at the end of each chapter.
Keywords: Civil Engineering